Analytical Profile of Vruntaka Phala Beeja (Solanum melongena Linn. Seeds): Life Sciences - P. Anjankar, Dr. Meghsham; Chalakh, Dr. Sonali; Chatuphale, Dr. Gajanan (International Journal of Life Science and Pharma Research, 2023)
Vruntaka Phala (Solanum melongena Linn.) is a well-known fruit vegetable available throughout the year in almost all parts of the country with diverse varieties. It has various nutritious as well as medicinal properties. In Ayurveda, it is mentioned as pathyakara (wholesome) in various disease conditions. As per modern dietetics, it is a rich source of dietary fibers and antioxidants which helps to prevent non-communicable diseases (NCDs’) like cancer, heart disease, diabetes, and hyperlipidemia. Solanum melongena is ranked amongst the top ten vegetables providing low calories and high phenolic contents, which help absorbtion of free radicals from the body. Besides this, it contains arginine, aspartic acid, histidine, oxalic acid, solasodine, ascorbic acid, tryptophan, pyrrolidine, and quinolizidine as important pharmacological active ingredients. By these phytoconstituents, the plant possesses proven pharmacological activities like antipyretic, analgesic, antioxidant, anti-inflammatory, antiasthmatic, spasmogenic, hypolipidemic, antihypertensive, thrombolytic, antiplatelet, calcium channel blocking, etc. Using these pharmacological activities, the plant can be used medicinally in treating disease conditions like fever, inflammation, neuralgia, asthma, etc. After a meticulous study of published data, it was found that the phytochemical constituents of most of the parts of Solanum melongena with their pharmacological activities were evaluated. But the physicochemical and phytochemical profile of Vruntaka Phala Beeja was rarely explained. Hence the present study aims to evaluate the analytical profile of Vruntaka Phala Beeja. The objective of the present study is to be acquainted with the nutritional, pharmacological, and medicinal properties of Solanum melongena.